Development of Learning Media Model for Creating Three-Dimensional Applied Art Works Based on Flipbooks in High School - Arwini, Dian; Djirong, Agussalim; Tangsi, Tangsi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The intent is to develop a valid, practical, and effective learning media model for creating three-dimensional applied artworks based on flipbooks at high school. This research is a research and development method that combines the ADDIE, 4D, and Borg & Gall models. This research was conducted at public high school 6 Bantaeng with a total of 25 research subjects of class XII and 1 art and culture subject teacher. The media experts' assessment yielded an average value of 4.3 for all aspects, indicating their high validity. The findings indicated that the assessment by the expert material validator yielded an average score of 4.9, placing it in the very valid category. The assessment results showed that art and culture teachers rated the practicality of the material with an average score of 4.8, which is considered excellent, while students gave an average score of 4.4, also in the excellent or very practical range. In the effectiveness aspect, the gain score calculation was carried out, and a score of 0.41 was obtained, which means that the learning media for creating three-dimensional applied art works based on flipbooks is in the moderate category. Therefore, it can be concluded that the learning media for creating three-dimensional applied art works based on flipbooks at public high school 6 Bantaeng is in the moderate and effective category.